Impact of Computerized Systems and Work Facilities on Employee Effectiveness: Moderating Role of Working Time - Siti Almaratus Solihah; Abriandi Abriandi (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
To analyze the effect of computerized systems and work facilities on work effectiveness among employees of PT Jasa Peralatan Pelabuhan Indonesia, with time at work as a moderator. Computerized System, Work Facilities, Work Effectiveness, Time Work Quantitative, SmartPLS, and Questionnaire. Computerized systems have a significant positive impact on work effectiveness. Work facilities also significantly impact work effectiveness. Working hours significantly impact work effectiveness. Working hours can moderate the impact of computerized systems on work effectiveness. Working hours also moderate the impact of work facilities on effectiveness. Research shows that both computerized systems and work facilities significantly impact work effectiveness, with working hours being a variable that strengthens this relationship. This study is limited to one company and respondent; therefore, the results cannot be generalized. Respondents were required from PT PELINDO employees, particularly PT Jasa Peralatan Pelabuhan Indonesia. All respondents were selected based on a strategy devised by Hair, which involved implementing a random employee sampling system.